Solomon Islands : 2008 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The 2008 Article IV Consultation with Solomon Islands discusses an economic outlook that hinges critically on developing nonlogging sources of growth and exports to offset the expected decline in logging activity. The country remains beset with poor infrastructure, land ownership issues, a shortage of skilled labor, and unreliable and costly basic services. Executive Directors recommended that the central bank seek to develop financial markets further and make greater use of interest rate mechanisms of monetary control. To avoid placing undue burden on monetary policy, fiscal policy needs to play a supportive role.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet